Multifunctional STING‐Activating Mn3O4@Au‐dsDNA/DOX Nanoparticle for Antitumor Immunotherapy. Issue 13 (2nd June 2020) - Zhou, Min; Wang, Xiaoyu; Lin, Shichao; Cheng, Yuan; Zhao, Sheng; Lin, Junshu; Fang, Zhuoyao; Lou, Zhangping; Qin, Li; Wei, Hui
Abstract: The promise of immunotherapy for cancer therapy has not been fully fulfilled because portions of tumors are immunosuppressive. To tackle this challenge, the initiation of immune system by stimulator of interferon genes (STING) pathway is explored and multifunctional STING‐activating nanoparticles are rationally designed for synergistic antitumor therapy. The STING‐activating nanoparticles have a formulation of Mn3 O4 @Au‐dsDNA/DOX, where dsDNA is used to activate STING for immunotherapy and doxorubicin (DOX) is chosen as a model drug for chemotherapy. The STING‐mediated immunity is activated, inducing interferon‐β (IFN‐β) production, increasing T cell priming, and enhancing effector T cell infiltration. Combined with chemotherapy, STING‐mediated immunotherapy shows good antitumor efficacy by inhibiting tumor growth and prolonging survival rate in vivo. The promise of cancer immunotherapy can be fulfilled by combining novel antitumor immunity with innovative nanotechnology, and chemotherapy and targeted therapies. Abstract : Stimulator of interferon genes (STING)‐activating nanoparticles for cancer immunotherapy: The first multifunctional STING‐activating Mn3 O4 @Au‐dsDNA/DOX nanoparticles are designed and synthesized, which successfully activate the STING‐mediated immunity and show synergistic antitumor efficacy in vivo.